Carbon Tax, Green Innovation, and Sustainable Development: Evidence from a Systematic Literature Review - Lady Karlinah; Meiriska Febrianti (Owner : Riset dan Jurnal Akuntansi, 2025)
This study employs a Systematic Literature Review (SLR) using the PRISMA framework to examine the role of carbon tax in fostering green innovation and advancing sustainable development. A total of 40 peer-reviewed articles published between 2015 and 2025 were analyzed from major databases including Scopus, Web of Science, and Google Scholar. The findings reveal that the carbon tax not only functions as a fiscal instrument to reduce carbon emissions but also acts as a catalyst for corporate green innovation and environmental disclosure practices. Three dominant themes emerged: (1) the effectiveness of carbon tax in reducing emissions and strengthening fiscal capacity, (2) its influence on corporate strategies to promote green technology and sustainable business models, and (3) its contribution to achieving the Sustainable Development Goals (SDGs), particularly in developing economies. While the carbon tax shows significant potential, challenges such as policy inconsistency, institutional weakness, and industrial resistance remain obstacles to its full implementation. The review offers guidance for policymakers to integrate fiscal and innovation policies toward sustainable growth.